Monopoly Game Design Krealand As a Learning Media in PKWU Subjects - Dyah Ayu Ratna Dewi; Godham Eko Saputro (Jurnal Penelitian Pendidikan, 2026)
Craft and Entrepreneurship (PKWU) learning still uses conventional approaches and does not utilize interactive learning media, so that student engagement in the learning process is not optimal. This study aims to develop a game-based learning media in the form of Monopoly Krealand in the PKWU subject. The study used the Research and Development (R&D) method with the ADDIE development model limited to the development stage. Data collection was carried out through observation, interviews with PKWU teachers, student needs analysis questionnaires, and expert validation questionnaires. The research respondents consisted of 35 grade X students and two expert validators. The data were analyzed quantitatively using a four-level Likert scale and descriptively qualitatively. The results of the needs analysis showed that 85% of students really needed interactive learning media. The results of the material expert validation obtained a feasibility level of 100% with a very feasible category, while the media expert validation obtained a percentage of 75% with a suitable category for use with revisions. Thus, Monopoly Krealand is declared to meet the feasibility criteria as a PKWU learning media and has the potential to support more interactive and contextual learning.